Comparison of Sexual Intimacy, Life Satisfaction and Coping Strategies with Postmenopausal and Non-Menopausal Women Referring To Health Centers - Soodabeh Bassak Nejad; Paryaa Ebadeh Avazi; Mahnaz Mehrabizadeh Honarmand (Hamadan University of Medical Sciences, 2019)
Introduction: Menopause is one of the stages of women's lives associated with physical and mental changes. The purpose of this study was to compare sexual intimacy, life satisfaction and coping strategies with postmenopausal and non-menopausal women referring to health centers of Ahvaz Oil Industry.   Methods: The research method was a descriptive-analytical one. The sample of this study was 200 postmenopausal and non-menopausal women who were selected via available sampling method in 2016. These groups were from the visitors to the petrochemical treatment centers who were matched by age, marital, economic and social status as well as physical health. The tools consisted of self-report questionnaire such as Bagarrozi intimacy needs questionnaire, life satisfaction questionnaire, and a Lazarus coping strategies questionnaire. SPSS18 was used for data analysis and the significance level was 0.05.   Results: The mean of sex intimacy score (P=0.001), life satisfaction (P=0.004), emotional coping strategies (P=0.04), and problem-oriented coping strategies (P=0.01) were significantly different in two groups.   Conclusion: After the onset of menopause, sexual intimacy and life satisfaction are reduced and preferably, according to psychological and physical changes, postmenopausal women use emotional-focused strategies to cope with stressful conditions.